Egressas de um Curso de Matemática e a Inclusão de Estudantes Autistas - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This work stems from the author’s perceptions regarding the inclusion of students with disabilities – especially those with Autism Spectrum Disorder (ASD) – in schools where she had the opportunity to work. Upon observing students with ASD and the different behavioral characteristics they displayed, several questions began to arise: How can Mathematics be taught to a student with ASD? Are the concepts discussed in the curricular component denominated Inclusive Education sufficient? These questions led to the general objective of this research: to understand how Mathematics teachers who graduated from the Federal University of Pampa (UNIPAMPA) work with the inclusion of students with ASD in the classroom. This is a qualitative study, and the data was collected through semi-structured interviews with four female graduates and one male graduate from the Mathematics Licentiate Program at UNIPAMPA, campus Bagé. Once transcribed, the interviews were analyzed based on the principles of Thematic Analysis. The study contributes to highlighting the practices, challenges, and perceptions of graduates of the Mathematics Licentiate Program in the process of including students with ASD. The participants’ statements underscore the need for more specific initial training on autism, as well as ongoing training opportunities, resources, and adequate classroom conditions, such as smaller class sizes and school support. Interviewees emphasized individualized planning and respecting students’ pace as key strategies for working with autistic students. The conclusion points to the urgency of broadening discussions on inclusion within teacher training programs at UNIPAMPA and investing in professional development initiatives that support inclusive teaching.
Keywords: Egressos; Professores de matemática; Autismo; Escola; Graduates; Mathematics teachers; Autism; School; CIENCIAS EXATAS E DA TERRA